IDENTIFIKASI POTENSI EKOWISATA SEBAGAI PENUNJANG KONSERVASI HUTAN MANGROVE DI DESA TELUK PAMBANG KECAMATAN BANTAN KABUPATEN BENGKALIS - Fanda Asnita Yusefa Ambarita; Defri Yoza; Rudianda Sulaeman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The mangrove forest is plants that live in the mouth of the river and were able to survive in the tide. The area has a mangrove ecosystem in Bengkalis is Teluk Pambang Village and need to be developed into the ecotourism area. Ecotourism development goal is to protect the existing potentials in the mangrove forests and became one of the alternative sources in raising funds for conservation activities. This research purpose to identify the ecotourism potential of mangrove forest in Teluk Pambang Village, Bantan District Bengkalis Regency, to knowing the efforts and forms of conservation for the development of ecotourism and  to knowing the correlation of ecotourism potential as a supporting mangrove forest conservation. The method that used in analyzing the potential of ecotourism is based on the analysis of mangrove vegetation that expressed in the formula English et al. (1997) to obtain density and the importance of community structure of mangrove conservation, efforts and  forms was processed using a Likert Scale and the relation of potential ecotourism as a supporting mangrove forest data was processed by descriptive. The results of this research indicate that the ecotourism potential of mangrove forest in the Teluk Pambang Village, consists of very density  mangrove forest. Station I had a density of 2,967 ind/ha, station II has a density of 5,778 ind/ha and Station III has a density of 4,688 ind/ha, vegetation and wildlife are varieties and landscape of ecotourism still nature. Efforts and forms of conservation were managed by the Manage Group of Mangrove (KPM) Belukap, habits and knowledges of local communities (local wisdom) in Teluk Pambang Village and participation of respondents to the conservation efforts. The correlation of ecotourism potential to support conservation of mangrove forests are a visitor, education and research. Keywords: Potential, Mangrove Ecosystem, Ecotourism, Conservation